The Head of Madrasah's Strategy in Developing A Culture of Love Reading The Quran - Muhammad Yusuf Siregar; Amiruddin Siahaan; Tien Rafida (Nidhomul Haq, 2021)
The madrasa principal's strategy is important in developing the goal of a culture of reading the Koran in Madrasahs. This article aims to explain the strategy of the head of the madrasa in developing a culture of reading pleasure at the Madrasah Aliyah Laboratory of UIN North Sumatra Medan. In order to achieve the research objectives, this research uses a qualitative approach with a descriptive method. Data collection techniques were carried out through observation, interviews, and documentation studies. The data analysis procedure is data reduction, data presentation, and conclusion drawing. While the research subjects were the head of the madrasa, deputy head of the madrasa, teachers, and students. The results showed that the strategies of the Head of Madrasah in developing a culture of reading the Qur'an at the Madrasah Aliyah Laboratory of UIN SU Medan were: 1). Give an example of a good attitude, 2). Good communication to all madrasa members, 3). Make madrasa regulations to be obeyed by educators, education staff, and students, 4). Motivating all educators, education staff, and students in the form of words, awards, and praise so that they do their job to the maximum extent possible. The head of the madrasa seeks to approach and motivate all educators and students to always be enthusiastic in cultivating a love of reading the Koran.